Followers’ Views on the Impact of Influencer Self-Disclosure in Advertising on Followership and Followers’ Decision to Buy the Advertised Brands - Baranauskaitė, Eglė (Vilnius University Open Series, 2025)
Influencers are intermediaries between the consumer and the brand who can influence the consumer’s purchasing decisions. Research suggests that influencers’ self-disclosure can have an impact. In the absence of a deeper insight into consumers’ attitudes towards the impact of this information on their purchase decision, the present study aims to identify the attitudes of the followers of influencer X in the study towards the impact of X’s different self-disclosures on X’s following, and on the decision to buy the brands X promotes. Interview participants revealed that self-disclosure information from all personality backgrounds is important for their X-following. The overlap between the self-disclosure information in the advertisement and in the profile is important for the participants. The importance of peripheral and intermediate personality layer information was related to trust in X. X’s attractiveness. They felt that X’s self-disclosure did not ensure X’s expertise. The positive effect of X’s self-disclosure in advertising on the purchase decision of the participants in the study was, in their view, related to the reproduction of peripheral personality information; the effect of intermediate personality information on the purchase decision was recognized in the interaction with X’s other profile information. It was found that if the participants in the study have a skeptical attitude towards influencer advertising, self-disclosure in advertising does not influence their purchase decision.